IMPLEMENTATION OF THE PROBLEM BASED LEARNING (PBL) MODEL OF THE TYRANY OF THE RISE SUN TO IMPROVE STUDENTS' LEARNING OUTCOMES OF CLASS X IPS 2 SMA NEGERI 1 KUTOREJO MOJOKERTO - Mardiyah Mardiyah (Sean Institute, 2022)
The purpose of this study was to determine the increase in student learning outcomes of class X IPS 2 SMA Negeri 1 Kutorejo, Mojokerto Regency through the application of a problem-based learning model to the subject of the tyranny of the rising sun. This research is a classroom action research with 2 cycles of improvement which includes the stages of planning, implementing, observing and reflecting. The action given is to apply the problem based learning model to the tyranny of the rising sun material. The research was conducted from April to May 2017 in class X IPS 2 at SMA Negeri 1 Kutorejo. The results showed that (1) the implementation of lesson plans showed that lesson plans could be implemented well and increased from an average score of 2.77 (good) in the first cycle to 3.31 (good) in the second cycle (2) student activity showed student centered learning ) with an activity percentage of 86.27% in the first cycle increased to 93.62% in the second cycle and students were very enthusiastic about listening to the information conveyed by the teacher, (3) Student responses after the application of the problem-based learning model used showed a positive response, and (4) The completeness of the results learning in cycle I individually has been achieved and classically has not been achieved, while in cycle II the completeness of learning outcomes both individually and classically has been achieved. Mastery learning outcomes achieved in the second cycle, increased from 77.77% in the first cycle to 91.66% in the second cycle.